The Impact of Business Process Reengineering on Organizational Performance - Khuzaimah, Ab-Llah (2011)
In Malaysia, the changing dynamics of banking and other financial institutions market forced players at all levels to reengineer their business organizations. The banking operations and functions which is intend to meet emerging challenges of bank consolidation, slashing operating cost, outsourcing, portfolio investment, payments and settlement system call for innovative banking practices through Business Process Reengineering. This is to enable Malaysian banks to incorporate strategic innovative customer schemes in order to bridge the service gap inherent in Malaysian banking sector. The objective of this paper is to assess the impact of reengineering on organizational performance and to uncover how Business Process Reengineering can help organizations to effect innovative and strategic changes in the organization. The data for this current investigation were obtained from primary source that was analyzed through simple percentage analysis and regression analysis. The paper concludes that Business Process Reengineering has become usehl weapon for any corporate organizations that is seeking for improvement in their current organizational performance and intends achieve cost leadership strategy in its operating industry and environment. It recommended that reengineering process remains effective tools for organizations striving to operate as effectively and efficiently as possible and organizations are required to reengineer their business processes in order to achieve breakthrough performance and long term strategy for organizational growth and performance.